Analysis of Harmonic Resonance for Locomotive and Traction Network Interacted System Considering the Frequency-Domain Passivity Properties of the Digitally Controlled Converter - Li, Jing; Liu, Qiujiang; Zhai, Yating; Molinas, Marta; Wu, Mingli (Frontiers in Energy Research, 2020)
Harmonic resonance is a kind of oscillatory instability phenomenon occurring in the electric railway. To investigate this problem, the frequency-domain model of the single-phase voltage source converter (VSC) for locomotives is derived based on the transfer function of the current control loop. The equivalent circuit of the traction network is also included in this frequency-domain model. Particularly, the time delay and zero-order-holder effect of the digital pulse width modulation (DPWM) are taken into consideration in order to obtain more accurate a model of the digital controller. After that, the harmonic resonance of the locomotive-network (L-N) system is assessed through the passivity properties of the interacted frequency-domain impedance model. Finally, the effectiveness of the theoretical analysis is demonstrated by simulations and experiments. As a result, the harmonic resonance can be predicted before a new electric railway is put into use so that some mitigation measures can be taken in advance.